(untitled) (Journal of the College of Basic Education, 2023)
Nations and peoples rise and their historical role in building human civilization increases with the amount of their interest in science and the level that its members reach as the basis of human progress. The appropriate educational model for the process of acquiring scientific concepts. Therefore, the process of forming scientific concepts and developing them among students is one of the objectives of teaching biology in all different stages of education. The process of forming or developing concepts among students requires an appropriate teaching method that ensures the integrity of concepts and their use in new situations.